RETRACTED: Pedagogical foundations in the teaching of folk arts and crafts of Uzbekistan in the training of teachers of fine arts - Abdullaev Sukhrob; Mamatov Dilshod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001